2008
DOI: 10.1111/j.1469-7998.2008.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal sharing between the European wildcat, the domestic cat and their hybrids

Abstract: The European wildcat Felis silvestris silvestris, which can hybridize with the domestic cat Felis catus to produce fertile hybrids, is threatened by hybridization. To identify the behavioural processes that can affect interbreeding, we investigated the spatio-temporal sharing between wildcats, domestic cats and their hybrids (defined on their genotypes) in a rural area of north-eastern France where hybridization is frequent. Wildcats' and hybrids' home ranges were larger than those of domestic cats, and they d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 21 publications
6
74
3
1
Order By: Relevance
“…We believe that the utilization of smaller forest fragments in our study is associated with the greater and more diverse food availability, especially small mammals, birds, insects and fruits, which are mainly associated with open farmland, urban residences, or other human-related resources (Tellería et al 1991;Austen et al 2001). This should also be true for the domestic cat Felis catus; however its activity is mainly concentrated in the vicinity of human settlements (Barratt 1997;Germain et al 2008).…”
Section: Discussionmentioning
confidence: 87%
“…We believe that the utilization of smaller forest fragments in our study is associated with the greater and more diverse food availability, especially small mammals, birds, insects and fruits, which are mainly associated with open farmland, urban residences, or other human-related resources (Tellería et al 1991;Austen et al 2001). This should also be true for the domestic cat Felis catus; however its activity is mainly concentrated in the vicinity of human settlements (Barratt 1997;Germain et al 2008).…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies clearly show that the development of more powerful tools is still critical to accurately identify parental and hybrid individuals of this species because of the high similarity in morphology and genomes of wild and domestic forms. Although microsatellites have been the dominant markers in wildcat genetic studies (for example, Beaumont et al, 2001;Randi et al, 2001;Pierpaoli et al, 2003;Lecis et al, 2006;Germain et al, 2008;Eckert et al, 2010;O'Brien et al, 2009), and recently mtDNA diagnostic SNPs have been suggested (Driscoll et al, 2011), the increasing availability and numerous advantages of nuclear SNPs make them an appealing alternative and/or a complement to maternal and paternal lineage markers. SNPs have been attracting a growing interest in a wide range of evolutionary applications and are becoming efficient tools among wildlife conservation-oriented studies (Brumfield et al, 2003;Morin et al, 2004;Seddon et al, 2005;Morin et al, 2009).…”
Section: Snp Simulations For Admixture Analysismentioning
confidence: 99%
“…Another determinant factor is the proximity of agricultural activity: in Corsican wild boar, seroprevalence was highest in counties with high farm densities [91]. The presence of domestic cats, including farm cats or feral cats essentially living on predation, and wildcats and hybrid that may live close to rural areas [113], is probably an important factor explaining the connection between the wild and domestic life-cycles of T.…”
Section: The Dynamics Of T Gondii In Wildlife In Temperate Climatesmentioning
confidence: 99%